Asymptotic representations of the solutions of essentially nonlinear nonautonomous second-order differential equations - Evtukhov, V. M.; Belozerova, M. A. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We establish asymptotic representations for the solutions of a class of nonlinear nonautonomous second-order differential equations.